Molecular Regulation of the Transition from Vegetative Growth to Meiosis in Plants and Model Organisms - Ammireddy Suguna; Gibence H. Rose Winnie (Archives of Current Research International, 2025)
This review examines the molecular mechanisms regulating the transition from vegetative growth to meiosis across plants and other eukaryotic models. It highlights key genetic pathways controlling floral meristem identity, ovule development, and meiotic entry, emphasizing conserved genes and regulatory networks in species like Arabidopsis, rice, yeast, and mice. The roles of hormonal signals, environmental cues, and nutrient sensing in meiosis initiation are discussed, along with mechanisms governing chromosome pairing, recombination, and segregation. Understanding these conserved processes offers insights into reproductive development and provides avenues for crop improvement and fertility management.